Behavior of COVID-19 in small municipalities (Research, Society and Development, 2022)
Objective: To evaluate the behavior of COVID-19 in small municipalities. Methods: Cross-sectional, retrospective study, with data from notification forms of the Notifica COVID-19 system of the 14th Health Regional Office of the State of Paraná, between March 2020 and May 2021, after which the data were analyzed in electronic spreadsheets, with prevalence and incidence calculation. The project was approved by the Research Ethics Committee. Results: Of the 86,848 charts analyzed, 21,061 were patients with a positive diagnosis for COVID-19. Of these, 16,114 were recovered patients, 4,504 with active disease, and 443 deaths. As for the incidence of cases, greater in 2021, in the months of February, March and May. The deaths occurred in those older than 20 years, 42% had comorbidities, highlighting: Hypertension, Diabetes Mellitus and Obesity. Conclusions: The regional analyzed, even not being one of the most populous, showed prevalence, incidence and mortality and the study contributed to alert health authorities to control transmission and intensification of restrictions.